Resistência e consentimento na empresa pós-fordista: uma etnografia com trabalhadores da Embraer - Oliveira, Marco Antonio Gonsales de (2017)
The objective of this thesis was to study the subjective relationships between workers and Embraer, a company aligned to post-Fordist management concepts. Through an ethnography along the lines of a case study extended for one year, I attended the spaces of conflict between capital and labor, I went to meetings at the Metalworkers Union of São José dos Campos, heard workers in the union as well as outside, I followed the demonstrations before and during the strikers movement, and talked and watched the workers in the productive and management sectors of Embraer. Through previous study of authors such as Antonio Gramsci (1978, 1984, 2004, 2008) and Michael Burawoy (2012, 2014), in addition to the main authors of critical theory in organizational studies, sociology, and interaction with working class, an interesting fact came to light: the subjective intentions proposed by post-Fordist companies are not as effective as many studies believe. There is no effectiveness of subjective intent over insecure working relationships. Much of the working class – an interesting fraction, explicitly the more insecure – are skeptical of the subjective proposals of companies, “We have a lot to lose, but what we have is still a lot” (Embraer worker celebrating the end of a strike). Workers are immersed in bourgeois hegemony articulated by through organic bourgeois intellectuals, subjectified by bourgeois values and social standards, but which do not show in their daily lives, in their discourse, and in their behavior the proposal of subjectivity that the company promotes. The insecure worker is more concerned with the objective ties of labor relations and less concerned with the emotional promises and bargains promoted by the company – after all, the goal is to be and remain employed. Even when consenting, many understand the situation of oppression and injustice that the reality of their work imposes. There is consent but little commitment, hence the fragility of the post-Fordist model of development, where the threshold between consenting and resisting is tenuous. On the other hand, in the studied conflict spaces, it is explained that, in an unprecedented way, there is a movement of “organized counterresistance” in search of consent and commitment: an organized trade union resistance movement. Leaders, managers, engineers, and technicians organized and confronted the union movement during the 2014 strikes at Embraer. Under the context of work insecurity, workers with “higher salaries”, who are also under threat, tended to adhere strongly to the subjective proposals of the company. When subaltern classes entered into conflict, those who earn “more pay” – the richer bourgeoisie – differentiate and distance themselves from the working class masses, being assimilated to hegemonic class values more easily, resisting and also struggling: they feared becoming a proletarian or a poor worker